1996
DOI: 10.1021/jo952048e
|View full text |Cite
|
Sign up to set email alerts
|

Hindered Rotation in Arylnaphthalene Lignans

Abstract: Many arylnaphthalene lignans show biological activity and although few of them contain stereogenic centers, they may nevertheless be chiral if there is hindered rotation about the aryl−naphthalene bond. A relatively high barrier to rotation may give rise to separable rotational enantiomers (atropisomers) which might have quite different pharmacological properties. In order to investigate this possibility we have synthesized the natural products justicidin A, justicidin B, retro-helioxanthin, retro-justicidin B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 17 publications
2
67
0
Order By: Relevance
“…8 These atropisomers interconvert slowly, hence permitting the two diastereomers observed in the NMR spectra, but the rotation barrier is too small for the individual diastereomers to be isolated at room temperature. 37 Compound 2 was isolated as an amorphous, colorless powder. The similar UV and IR spectra to those of 1 indicated that 2 is also an arylnaphthalene lignan lactone.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…8 These atropisomers interconvert slowly, hence permitting the two diastereomers observed in the NMR spectra, but the rotation barrier is too small for the individual diastereomers to be isolated at room temperature. 37 Compound 2 was isolated as an amorphous, colorless powder. The similar UV and IR spectra to those of 1 indicated that 2 is also an arylnaphthalene lignan lactone.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…33 Based upon Charlton's studies, we designed lamellarin analogues (1) and (2) having 1,3-benzodioxol-5-yl group at the C1 position ( Figure 2). These compounds may be suitable for VT NMR experiments, because two substituents R on the 1,3-benzodioxol-5-yl group are diastereotopic each other and, therefore, the chemical shifts of the substituents R in NMR spectra should be different, if rotation around C1-C11 single bond…”
Section: Resultsmentioning
confidence: 99%
“…Diphyllin was prepared according to the procedure reported previously. 14) Nextly, hydrazide 1 was obtained as yellow solid in 87% yield by the reaction of diphyllin with excess hydrazine hydrate in ethanol over a 6 h reflux period. The structure of compound 1 was confirmed by mass spectroscopy and H-NMR spectra indicated the chemical shift of the NH 2 proton at dϭ4.46 ppm in the form of singlet peak.…”
Section: Resultsmentioning
confidence: 99%